Transparency and accountability in Brazilian National Sport Organisations - Gustavo Bavaresco; Geoff Dickson; Philipe Camargo; Thiago Santos; Fernando Marinho Mezzadri (Cogent Social Sciences)
This study examines the prevalence of transparency and accountability in Brazilian National Sports Organizations. Transparency is an organization’s ability to acquire and disseminate accurate and relevant information and knowledge. Accountability refers to an organization’s duty or obligation to provide an account or explanation of their actions. Both transparency and accountability are associated with modernization and good governance. In this study, we collected annual indicators of transparency and accountability between 2015 and 2021 for 34 Brazilian National Sports Organizations. Data were analyzed using Generalized Estimating Equations (GEE). The three key findings of the research were as follows: (1) transparency and accountability increased over the years; (2) there was selective growth in transparency and accountability dimensions; and (3) there was stagnation for audit (AUD), an accountability indicator. These findings suggest that the modernization of Brazilian National Sports Organizations is underway, but there is still potential for improvement.